THE APPLICATION OF INDIRECT BOUNDARY ELEMENT METHOD ON ELECTROSTATIC FIELD PROBLEMS - Ekici, Sami; Yildirim, Selcuk (Pamukkale Univ, 2007)
In this study, the analysis of the electric field problems has been performed by using indirect boundary element method. The main purpose of this study is to demonstrate indirect boundary element method which is a numerical method used in the electrostatic field calculations is an effective method. Firstly, the mathematical formulations of the method have been demonstrated. In application section, the analysis of transmission line model which has parallel two wires and infinite length has been performed by using ISEY. The obtained results are compared with ELECTRO software's results. According to result, it is seen that the indirect boundary element method performs more accurate calculations for two dimensional electrostatic field problems; on the other hand it provides user easiness of solution.
Keywords: Boundary element method; Indirect boundary element method; Electrostatic fields